UJI BIODEGRADASI PLASTIK BIODEGRADABEL DARI LIMBAH POLIPROPILENA DAN PATI BIJI DURIAN SEBAGAI BAHAN PENGISI - Pelita, Elda; Hidayani, Tengku Rachmi; Nirmala, Dyah (Politeknik ATI Padang, 2017)
This research was conducted with the aim to produce a biodegradable plastic from waste plastic polypropylene mixing with the starch of durian seeds by adding maleic anhydride as a crosslinking agent, and benzoyl peroxide as initiator. In this study, carried out with a variety of ingredients are added with a certain ratio that is successively waste Polypropylene, starch from durian seeds, maleic anhydride and benzoyl peroxide are (94:6:1), (94:6:1:1), (94:6:2:1), (94:6:3:1). Biodegradable plastic in the characterization of the analysis with the ability to decompose in nature biodegradable test, with embedding samples of biodegradable plastic produced into three types of soil, namely normal soil, ground litter and sand for 1 month. Each sample was observed a decrease in mass every 10 days. From Biodegradabel in nature results obtained mass loss that has been grown for 1 month is on the ground litter by 9.08% in the sample by varying the composition (94:6:1:1).